Gross Anatomy of the Heart of Pampas Deer (Ozotoceros bezoarticus, Linnaeus 1758) - Vazquez, Noelia; Dos Santos, Dellis; Pérez, William; Artigas, Rody; Sorriba, Victoria (Journal of Morphological Sciences, 2019)
The pampas deer belongs to the Cervidae family (Artiodactyla order). It used to be a common and abundant species that had a wide distribution. However, at the end of the 19th century, the populations were decimated. In general, the hearts of mammals share many similarities, but size, shape, position, vessel organization and branching can vary among species. The objective of the present study was to describe the macroscopic morphology, topography and irrigation of the heart of the pampas deer. The anatomical study was conducted with 20 animals that had died of natural causes. The animals were studied by simple dissection. All animals had colored latex injected into one of the common carotid arteries to facilitate the visualization. The position of the heart, with a 45° axis, the presence of a double sternopericardial ligament, and the bilateral cardiac circulation were some of the notable findings.
Keywords: atrium; cervidae; coronary artery